Global functional connectivity reorganization reflects cognitive processing speed deficits and fatigue in multiple sclerosis - Hok, Pavel; Thai, Quang Thong; Bučková, Barbora Rehák; Domin, Martin; Řasová, Kamila; Tintěra, Jaroslav; Lotze, Martin; Grothe, Matthias; Hlinka, Jaroslav (European journal of neurology, 2025)
BACKGROUND AND PURPOSE: Cognitive impairment (CI) in multiple sclerosis (MS) is associated with bidirectional changes in resting-state centrality measures. However, practicable functional magnetic resonance imaging (fMRI) biomarkers of CI are still lacking. The aim of this study was to assess the graph-theory-based degree rank order disruption index (kD) and its association with cognitive processing speed as a marker of CI in patients with MS (PwMS) in a secondary cross-sectional fMRI analysis. METHODS: Differentiation between PwMS and healthy controls (HCs) using kD and its correlation with CI (Symbol Digit Modalities Test) was compared to established imaging biomarkers (regional degree, volumetry, diffusion-weighted imaging, lesion mapping). Additional associations were assessed for fatigue (Fatigue Scale for Motor and Cognitive Functions), gait and global disability. RESULTS: Analysis in 56 PwMS and 58 HCs (35/27 women, median age 45.1/40.5 years) showed lower kD in PwMS than in HCs (median -0.30/-0.06, interquartile range 0.55/0.54; p = 0.009, Mann-Whitney U test), yielding acceptable yet non-superior differentiation (area under curve 0.64). kD and degree in medial prefrontal cortex (MPFC) correlated with CI (kD/MPFC Spearman's ρ = 0.32/-0.45, p = 0.019/0.001, n = 55). kD also explained fatigue (ρ = -0.34, p = 0.010, n = 56) but neither gait nor disability. CONCLUSIONS: kD is a potential biomarker of CI and fatigue warranting further validation.
Keywords: Magnetic Resonance Imaging; magnetická rezonanční tomografie; Humans; fatigue; lidé středního věku; Multiple Sclerosis; biomarkers; Female; cognitive processing speed; dospělí; lidé; Fatigue; fMRI; Processing Speed; Adult; ženské pohlaví; multiple sclerosis; roztroušená skleróza; Male; Middle Aged; Cognitive Dysfunction; únava; Cross-Sectional Studies; rychlost zpracování; mužské pohlaví; kognitivní dysfunkce; průřezové studie